The Influence of Sodium Chloride Treatment on the Sisal Fiber Bundle’s Properties - Setyayunita, Tamaryska; Suryanto, Heru; Aminnudin, Aminnudin (Universitas Negeri Malang, 2024)
Currently, composite board manufacturing using natural fiber has the potential to be expanded due to environmental awareness. To produce high-performance natural fiber, treatment is needed to improve natural fiber’s mechanical and physical properties. One of chemical treatments is by using sodium chloride (NaCl). This study aimed to investigate the characteristics of sisal fiber after NaCl treatment. The concentrations of NaCl treatment were 1, 3, and 5 (wt.%) at room and boiling temperature and the soaking duration was 1 hour. Meanwhile, tensile strength, strain, and Young’s modulus were tested to evaluate the mechanical properties. Fiber bundle diameter, weight change due to treatment, and contact angle were tested to assess the effect of NaCl treatment. Sisal fiber bundle was treated with 5 wt.% NaCl for 1 h exhibited the highest value of tensile strength, Young’s modulus, reduction of fiber bundle diameter, percentage of weight change, and decrement of contact angle in comparison with untreated fiber bundle. Treatment with 5 wt.% NaCl at boiling temperature successfully increased the tensile strength and Young's modulus by 48.39% and 76.8%, respectively, compared to untreated fibers. NaCl treatment was shown to be an effective method to improve the mechanical properties and wettability of fibers, which has potential for application in high-performance plant fiber composites. The surface of sisal fiber treated with 5 wt.% NaCl at boiling temperature appeared rougher than that of the untreated one. In addition, this treatment also reduced the contact angle between the fiber and the adhesive by 38.71% compared to the untreated.